Anti-obesity activities of n-hexane fraction of Pterocarpus mildbraedii leaves on obese male rats - Sarah A. AKANDE; Uju D. ILIEMENE; Gideon A. GYEBI; Gabriel O. ANYANWU (Notulae Scientia Biologicae)
This study investigated the in vivo anti-obesity potentials of n-hexane fraction of Pterocarpus mildbraedii Harms in high fat diet induced obese rats. Gas chromatography mass spectrometry analysis showed eighteen peaks depicting the presence of seventeen bioactive compounds. Oral administration of n- hexane fraction of P. mildbraedii resulted in an appreciable loss (p < 0.05) in body and organ weight, significant improvement (p < 0.05) in blood lipid profile, characterized by decreased serum levels of triglycerides, total cholesterol, and low-density lipoprotein cholesterol, significantly lower (p < 0.05) glucose, insulin, and leptin levels, in contrast with adiponectin level. Moreover, treatment with n-hexane fraction of P. mildbraedii led to a significant (p < 0.05) downregulation of adipogenic genes and an upregulation of lipolytic genes via the AMPK signalling pathway. Additionally, histological examination showed the ameliorative effect of the fraction on liver and adipose tissues. Conclusively, results from this study propose P. mildbraedii as a viable option for the treatment and management of obesity, because it effectively reduced body weight, enhanced lipid profile, inhibit lipogenesis and promote lipolysis.